Поселения черняховской культуры Шлях 2 и Халимоновка на Мже - Любичев, М.В. (My University, 2005)
M. Liubichev. Shlyah–2 and Halimonovka on Mzha-river, the Settlements of Chernyahov Culture In 2001–2002, the Slavonic Archaeological Expedition of Kharkov’s National University excavated Shlyah–2 and Halimonovka (Valki County, Kharkov region), the settlements of Chernyahov Culture. Both settlements are situated on black earth slopes of a water-supplied gully. In Halimonovka, two dwellings were researched. All of the pottery discovered there were wheel-made and could be classified as cooking ware (pots), coarse ware (bowls, vessels, pitchers, cups) and transport/storage ware (amphorae and pithos). Amphora fragments belong to light-clay amphora type F. Clay bead, fragment of glass beaker type (Eggers 230), bronze fibula type B3e (by Gorohovski), bronze buckle type G (by Gorohovski), iron arrow head, iron knives, awls and nails were found during the excavation and Denarius of Marcus Aurelius and Commodus were found at surface level. In Shlyah–2 all of the ceramics also wheel made. Fragments of amphorae type F and E, type Delakeu (Zeest 100), different types of spindle whorls, loom-weights, spiral drill, blank for fibula of «military» type and a glass bead were found. Dating for Shlyah–2 is proposed as second half of IV — beginning of V centuries. Halimonovka should be dated as the end of IV — beginning of V centuries. Both are late settlements of Chernyahov Culture of a C3–D1 of European Chronology.